A practical approach in bioreactor scale‐up and process transfer using a combination of constant P/V and vvm as the criterion. (14th May 2017) - Xu, Sen; Hoshan, Linda; Jiang, Rubin; Gupta, Balrina; Brodean, Eric; O'Neill, Kristin; Seamans, T. Craig; Bowers, John; Chen, Hao
Abstract : Bioreactor scale‐up is a critical step in the production of therapeutic proteins such as monoclonal antibodies (MAbs). With the scale‐up criterion such as similar power input per volume or O2 volumetric mass transfer coefficient ( k L a ), adequate oxygen supply and cell growth can be largely achieved. However, CO2 stripping in the growth phase is often inadequate. This could cascade down to increased base addition and osmolality, as well as residual lactate increase and compromised production and product quality. Here we describe a practical approach in bioreactor scale‐up and process transfer, where bioreactor information may be limited. We evaluated the sparger k L a and k L a C O 2 (CO2 volumetric mass transfer coefficient) from a range of bioreactor scales (3–2, 000 L) with different spargers. Results demonstrated that k L a for oxygen is not an issue when scaling from small‐scale to large‐scale bioreactors at the same gas flow rate per reactor volume (vvm). Results also showed that sparging CO2 stripping, k L a C O 2, is dominated by the gas throughput. As a result, a combination of a minimum constant vvm air or N2 flow with a similar specific power was used as the general scale‐up criterion. An equation was developed to determine the minimum vvm required for removing CO2 produced from cell respiration. We demonstrated the effectiveness of using such scale‐up criterion with five MAb projects exhibiting different cell growth and metabolic characteristics, scaled from 3 to 2, 000 L bioreactors across four sites. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:1146–1159, 2017